Pendidikan Anak Usia Dini: Perannya dalam Membangun Karakter dan Tumbuh Kembang Anak Usia Dini - Nabila Putri Widya Ningrum; Fatma Mayang Jelita Pane; Seri Indah Yani; Khadijah (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
This article discusses the role of early childhood education in building character and early childhood development. In accordance with what was expressed by Kihajar Dewantara, that everyone is a teacher, and every place is a school, this shows that education can be obtained from anyone and anywhere. Can be from family and also the surrounding environment. In general, the first education in educating children's character starts from the family. The family becomes the main madrasa in instilling the seeds of children's character. To develop the character of the child, environmental factors play an important role in it. One of the environments that can develop children's character is Kindergarten Education. This education will stimulate children's development through various media which will later be useful for developing the character and potential of early childhood.